2022
DOI: 10.3390/su15010569
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aeolian Sand and Water−Cement Ratio on Performance of a Novel Mine Backfill Material

Abstract: The gob-side entry retaining (GER) technique, as the family member of the pillarless coal mining system, is becoming popular, mainly attributed to its high resource recovery rate and significant environmental benefits. Seeking cost-effective backfill material to develop the roadside backfilling body (RBB) is generally a hot topic for coal operators and scholars. Except for its relatively high cost, the other shortcoming of the widely used high-water backfill material is also obvious when used in arid, semi-ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…When the porosity in from 0.3 to 0.34, the values of uniaxial compressive strength of specimens H-1-00, and H-1-60 decreased by 16.90%, 24.30%, and 28.01%, respectively. Research on desert sand concrete has shown that the optimal sand content of desert sand is between 20 and 60%, and the numerical simulation results are approximately the same as the experimental results [30,35]. When the desert sand content is low, the compressive strength of the specimen decreases slightly.…”
Section: Effect Of Porosity On Uniaxial Compressive Strengthsupporting
confidence: 54%
See 3 more Smart Citations
“…When the porosity in from 0.3 to 0.34, the values of uniaxial compressive strength of specimens H-1-00, and H-1-60 decreased by 16.90%, 24.30%, and 28.01%, respectively. Research on desert sand concrete has shown that the optimal sand content of desert sand is between 20 and 60%, and the numerical simulation results are approximately the same as the experimental results [30,35]. When the desert sand content is low, the compressive strength of the specimen decreases slightly.…”
Section: Effect Of Porosity On Uniaxial Compressive Strengthsupporting
confidence: 54%
“…Research on desert sand concrete has shown that the optimal sand content of desert sand is between 20 and 60%, and the numerical simulation results are approximately the same as the experimental results [ 30 , 35 ]. When the desert sand content is low, the compressive strength of the specimen decreases slightly.…”
Section: Analysis Of Influencing Factorsmentioning
confidence: 60%
See 2 more Smart Citations